Industrial Wastes as Auxiliary Additives to Cement/Lime Stabilization of Soils - Jijo James; P. Kasinatha Pandian (Advances in Civil Engineering)
Chemical stabilization involves the use of chemical agents for initiating reactions within the soil for modification of its geotechnical properties. Cement and lime stabilization have been the most common stabilization methods adopted for soil treatment. Cement stabilization results in good compressive strengths and is preferred for cohesionless to moderately cohesive soil but loses effectiveness when the soil is highly plastic. Lime stabilization is the most preferred method for plastic clays; however, it proves to be ineffective in sulphate rich clays and performs poorly under extreme conditions. With such drawbacks, lots of researches have been undertaken to address the issues faced with each stabilization method, in particular, the use of solid wastes for soil stabilization. Solid waste reuse has gained high momentum for achieving sustainable waste management in recent times. Research has shown that the use of solid wastes as additives with and replacement for conventional stabilizers has resulted in better results than the performance of either individually. This review provides insight into some of the works done by earlier researchers on lime/cement stabilization with industrial wastes as additives and helps to form a sound platform for further research on industrial wastes as additives to conventional stabilizers.